Muhammadiyah's View of the Pancasila State in the Dynamics of Diversity in Indonesia after the 2015 Congress - Muhammad Lukman Hakim; David Efendi; Alam Mahadika (Indonesian Academy of Social and Religious Research (IASRR), 2020)
Indonesia is a multiculturalist country by placing Pancasila as the main milestone in formulating all attitudes towards the nation and state, which are expected to inherit a nation's noble and noble culture. Pancasila contains values ​​that are very noble and do not conflict with religious and social values. The motto